Sensitized near-infrared lanthanide luminescence from Nd(III)- and Yb(III)-based cyclen-ruthenium coordination conjugates. - Sénéchal-David, K; Pope, S; Quinn, S; Faulkner, S; Gunnlaugsson, T (2006)
The development of novel mixed lanthanide-transition-metal (f-d) based supramolecular self-assemblies made from neodymium- and ytterbium-based tetraamide-functionalized cyclen complexes bearing a single 1,10-phenanthroline moiety coordinating to a RuII(bipy)2 (bipy = bipyridine) unit is described. Excitation of the Ru(II) metal-to-ligand charge-transfer band in water gave rise to long-wavelength sensitized emission from the Yb(III) or Nd(III) centers, observed in the near-infrared.